A Quattroplast Kft. kimenő és bejövő logisztikája - Pregitzer Annamária (2016)
The aim of my Thesis is to present the inbound and outbound logistics of Quattroplast Co. Ltd., in addition to analyzing the company’s economy. By the choice of thesis topic I have tried to give a comprehensive picture of the economic and commercial activities in a plastics trading business, affecting the logistics processes. In my topíc selection also played a decisive role that int he company in question (which is my workplace). I am involved int he analysed processes at issue, and it helped me to understand the operations, during the professional practice. I looked for the answer for the question how the company would be able to devalop his logistics going out even better primarly in my paper, and inside this the customers service.